2021
DOI: 10.1186/s13568-021-01189-6
|View full text |Cite
|
Sign up to set email alerts
|

Classification of acetic acid bacteria and their acid resistant mechanism

Abstract: Acetic acid bacteria (AAB) are obligate aerobic Gram-negative bacteria that are commonly used in vinegar fermentation because of their strong capacity for ethanol oxidation and acetic acid synthesis as well as their acid resistance. However, low biomass and low production rate due to acid stress are still major challenges that must be overcome in industrial processes. Although acid resistance in AAB is important to the production of high acidity vinegar, the acid resistance mechanisms of AAB have yet to be ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 137 publications
0
63
0
Order By: Relevance
“…During oxidation, these bacteria convert ethanol and sugars into aldehydes, ketones, and organic acids ( Wang et al 2015 ). Currently, 19 genera and 92 species of acetic acid bacteria have been discovered ( Qiu et al 2021 ). The conversion of ethanol into acetic acid by acetic acid bacteria has broad applications.…”
Section: Introductionmentioning
confidence: 99%
“…During oxidation, these bacteria convert ethanol and sugars into aldehydes, ketones, and organic acids ( Wang et al 2015 ). Currently, 19 genera and 92 species of acetic acid bacteria have been discovered ( Qiu et al 2021 ). The conversion of ethanol into acetic acid by acetic acid bacteria has broad applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a total of 127 ORFs were further identified as CAZymes, while 43 auxiliary carbohydrate-metabolism genes were identified in vinegar Pei viruses, which belong to AAs, CEs, GHs, GTs and PLs family, including the common alcohol oxidases, acetylesterase, cellulase, peptidoglycan lytic transglycosylases, mannanase, chitinase, glucosyltransferase, starch phosphorylase, glucan synthase and pectate lyase ( Table 2 ). Among them, alcohol oxidases are key enzymes in acetic acid synthesis [ 30 ]. Cellulose-rich materials such as wheat bran and rice hulls are raw materials of Zhenjiang aromatic vinegar in the acetic acid fermentation process.…”
Section: Resultsmentioning
confidence: 99%
“…In the study, the higher relative abundance (RA) of Acetobacter in CON of NFI silage might be associated with the higher AA than other silages. Qiu et al 42 . reported that although Acetobacter can oxidize ethanol or LA to AA, the accumulation of AA causes acid stress that inhibits Acetobacter .…”
Section: Discussionmentioning
confidence: 99%